Peran Kepemimpinan Islam dalam Meningkatkan Karakter dan Etos Belajar Siswa di Lembaga Pendidikan Islam - Muhammad Fauzan (STIT Muhammadiyah Bangil Pasuruan, 2024)
The function of leadership within Islamic educational institutions serves as a crucial element for the progression of these establishments. As a leader, every policy enacted will greatly influence the caliber of the staff. This study endeavors to analyze the leadership function within Islamic educational institutions utilizing a qualitative research approach. Data is collected through observations and interviews. The enactment of character education has been stipulated by Law Number 20 of 2003 regarding the National Instruction Framework, which asserts that